The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1089/jpm.2013.0196
|View full text |Cite
|
Sign up to set email alerts
|

Informal Caregiving of Hospice Patients

Abstract: Beyond satisfaction with hospice services, the direct impact of standard hospice care on caregivers remains uncertain. Caregiver intervention studies have demonstrated promising outcomes signifying a need for additional investigations into hospice-specific interventions that improve caregiver outcomes. Additional research and resources are needed to assist hospice caregivers, with the ultimate goal of minimizing their psychiatric and physical morbidity and enhancing their caregiving and subsequent bereavement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 77 publications
3
51
0
2
Order By: Relevance
“…23,24 Therefore, it is not uncommon for many to experience significant anxiety, depression, and stress during the caregiving process. 25 Our analysis reveals that caregivers with high burden levels may decide to hospitalize patients because they feel overwhelmed. While hospice care aims to be comprehensive, standard home hospice care may not be sufficient for all patients and caregivers.…”
Section: Challenges Faced By Caregiversmentioning
confidence: 92%
See 1 more Smart Citation
“…23,24 Therefore, it is not uncommon for many to experience significant anxiety, depression, and stress during the caregiving process. 25 Our analysis reveals that caregivers with high burden levels may decide to hospitalize patients because they feel overwhelmed. While hospice care aims to be comprehensive, standard home hospice care may not be sufficient for all patients and caregivers.…”
Section: Challenges Faced By Caregiversmentioning
confidence: 92%
“…Many patients trust their physicians and highly value that continuity. 16,[23][24][25] Further research is needed to understand how patients' and families' preferences to maintain care with their physicians influences hospitalization patterns. Developing ways to better integrate nonhospice physicians within hospice care may reduce patients' and families' desire to be hospitalized when care can be delivered within hospice.…”
Section: Creating Better Transitions Into Hospicementioning
confidence: 99%
“…124,125 Limited and conflicting evidence supports the ability of palliative care programs to reduce burden among caregivers of patients with advanced HF. 126,127 Abernethy et al 120 found that bereaved caregivers of patients receiving specialized palliative care services for a terminal illness were more likely to report having "moved on" after the loss of their loved one.…”
Section: Caregiver Outcomesmentioning
confidence: 99%
“…These findings meet the "Research Recommendations for Improving the Assessment of the Prevalence and Burden of Informal Cancer Caregiving" [86], emphasizing the need to direct attention towards the most vulnerable caregivers of cancer patients, such as those socially isolated, living in rural areas, or with low socioeconomic status. Social isolation and low appraisal of caregiving, along with depression, financial stress, and lack of choice in being a caregiver, are important risk factors of caregiver strain, affecting their burden perception [87,88].…”
Section: Discussionmentioning
confidence: 99%